'A fair day's work for a fair day's pay' or 'working for love and not money'? Using class actions to challenge the labour law exclusion in Minor League Baseball in the United States. (3rd July 2018) - Nichol, Matt
ABSTRACT: Major League Baseball (MLB) annually generates US9 billion in revenue and the average salary for a professional player is nearly US4 million, with some earning over US20 million per year. Minor League Baseball (MiLB), which acts as a development channel for MLB teams, is also lucrative and teams can generate millions from attendance, advertising and merchandise. Yet MiLB players are paid only between US1, 100 and US2, 150 per month during the season. Like many athletes and artists who are either specifically excluded from labour laws or fall outside their scope because they are not seen as employees, MiLB players are marginalised by antitrust and labour laws, a position reinforced by their exclusion from the Major League players' association and the absence of collective bargaining. Barriers to legal recourse exist for Minor League players in the form of federal antitrust law exemption and a new exemption from federal labour law introduced in 2018. This article examines the plight of Minor League players and their response in accessing a fair wage or a 'living' wage through the use of class actions in antitrust law and federal labour law.